Design a self-compacting concrete (scc) using local materials-study on workability and compressive strength - I.H, Achong (Universiti Malaysia Sarawak, UNIMAS, 2000)
The main objectives of this project are to design self-compacting concrete using local material and study on work-ability and compressive strength designed by SCC